I survived : the Nazi invasion, 1944 - Ball, Georgia (I survived (Graphic novel series), 2021)
After their father is taken by the Nazis, Polish Jews Max Rosen and Zena, his sister, escape their ghetto into the woods. There they find a safe camp of other Jewish resistance fighters--but this by no means makes them any safer.